Cholinergic Depletion in Alzheimer's Disease Shown by [18F]FEOBV Autoradiography. (10th November 2013) - Parent, Maxime J.; Bedard, Marc-Andre; Aliaga, Arturo; Minuzzi, Luciano; Mechawar, Naguib; Soucy, Jean-Paul; Schirrmacher, Esther; Kostikov, Alexey; Gauthier, Serge G.; Rosa-Neto, Pedro
Abstract : Rationale . Alzheimer's Disease (AD) is a neurodegenerative condition characterized in part by deficits in cholinergic basalocortical and septohippocampal pathways. [ 18 F]Fluoroethoxybenzovesamicol ([ 18 F]FEOBV), a Positron Emission Tomography ligand for the vesicular acetylcholine transporter (VAChT), is a potential molecular agent to investigate brain diseases associated with presynaptic cholinergic losses. Purpose . To demonstrate this potential, we carried out an [ 18 F]FEOBV autoradiography study to compare postmortem brain tissues from AD patients to those of age-matched controls. Methods . [ 18 F]FEOBV autoradiography binding, defined as the ratio between regional grey and white matter, was estimated in the hippocampus (13 controls, 8 AD) and prefrontal cortex (13 controls, 11 AD). Results . [ 18 F]FEOBV binding was decreased by 33% in prefrontal cortex, 25% in CA3, and 20% in CA1. No changes were detected in the dentate gyrus of the hippocampus, possibly because of sprouting or upregulation toward the resilient glutamatergic neurons of the dentate gyrus. Conclusion . This is the first demonstration of [ 18 F]FEOBV focal binding changes in cholinergic projections to the cortex and hippocampus in AD. Such cholinergic synaptic (and more specifically VAChT) alterations, in line with the selective basalocortical and septohippocampal cholinergic losses documented in AD, indicate that [ 18 F]FEOBV is indeed a promising ligand to explore cholinergic abnormalities in vivo .